2023
DOI: 10.21203/rs.3.rs-2460926/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Prospective Study of Chronic Postsurgical Pain in Elderly Patients: Prevalence, Characteristics and Risk factors

Abstract: Background Considering the continued growth of surgical procedures in older adults and the significant impact of chronic postsurgical pain (CPSP), it is crucial to improve our understanding of the occurrence of CPSP as well as the appropriate prevention and treatment. We therefore conducted this study to determine the prevalence, characteristics and risk factors of CPSP in elderly patients at both 3 and 6 months after surgery. Methods Elderly patients (aged ≥ 60 years) undergoing elective surgery in our insti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Recently, the postoperative occurrence of pruritus in the painful area as well as cold hypersensitivity 14 days after surgery were shown to be associated with the development of CPSP [47 ▪▪ ]. The role of these neuropathic pain features assessed after surgery in the prognostication of CPSP emphasizes the role of surgery-induced neuropathic mechanisms [62,63]. Similar, assessment of a neuropathic pain questionnaire, the DN4 early after surgery was associated with the development of neuropathic CPSP [64].…”
Section: Mechanisms Behind Prognostic Factors For Chronic Postsurgica...mentioning
confidence: 91%
“…Recently, the postoperative occurrence of pruritus in the painful area as well as cold hypersensitivity 14 days after surgery were shown to be associated with the development of CPSP [47 ▪▪ ]. The role of these neuropathic pain features assessed after surgery in the prognostication of CPSP emphasizes the role of surgery-induced neuropathic mechanisms [62,63]. Similar, assessment of a neuropathic pain questionnaire, the DN4 early after surgery was associated with the development of neuropathic CPSP [64].…”
Section: Mechanisms Behind Prognostic Factors For Chronic Postsurgica...mentioning
confidence: 91%
“…CPSP may result from the accumulation of inflammatory cytokines during surgery and after surgery in the setting of PPA, thereby sensitizing the peripheral and central nervous systems. 10,11 Although the current study was not designed to identify methods of avoiding PPA, the strong relationship that was identified between PPA and COU suggests that the management of acute postsurgical pain should be a continued research focus and a clinical priority. This study identified demographic factors associated with COU.…”
Section: Figurementioning
confidence: 98%
“…The relationship between PPA and CPSP, leading to COU, is well documented. 1,3,4,9,10 Previous studies have suggested mechanistic explanations of the relationship between PPA and CPSP. CPSP may result from the accumulation of inflammatory cytokines during surgery and after surgery in the setting of PPA, thereby sensitizing the peripheral and central nervous systems.…”
Section: Figurementioning
confidence: 99%
“…Typical and easy-to-assess patient-related prognostic and risk factors for CPSP are young (adult) age, female sex, and high BMI (see Table 2). While young (adult) age is a well-described associated factor for the development of acute and (not as strong) for CPSP ( 6,95,100▪▪ ; see Tables 1 and 2), elderly patients present particular susceptibility associated with comorbidities, but also more prevalent central sensitization and changes in the descending modulating systems 101,102 . Thus, the role of age for CPSP needs further exploitation.…”
Section: Preoperative Patient-related Factorsmentioning
confidence: 99%